A Survey on Technology used in Higher Secondary EFL Class in Bangladesh - Fatema, Kaniz; Sultana, Negar (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: The paper aims to present an overview of the technologies that are used in English language learning classes in Higher Secondary Level of Studies in Bangladesh. The aim is also to identify the gaps between the use of technology and CLT- based curriculum and material. Approach/Methodology/Design: Four colleges were selected randomly as a sample of the study. For collecting data, an open-ended questionnaire was constructed, validated, and administrated. In addition, structured interviews and an observation guide of classes were employed as instruments to collect data. Findings: Based on the results of data analysis, it is clear that the use of technology in Bangladesh is increasing day by day but the percentage is still very low. The results of this study indicate that there is a gap between the use of technology and CLT based curriculum and material in Bangladesh. Hence, it is concluded that the technologies that are used in the classrooms are not adequate. Practical Implications: The study reflects on the use of technology in classrooms. This is in line with the mission of digital Bangladesh. Originality/value: This study is important for teachers, students and authorities since it reflects on the technology being used in higher secondary level, the gaps between the use of technology and CLT- based curriculum and material in Bangladesh and how the gap can be fulfilled to ensure the proper use of technology in CLT- based educational environment and attain the vision of ‘Digital Bangladesh’.